Correction: Embo-Ibouanga et al. Peptide-Alkoxyamine Drugs: An Innovative Approach to Fight Schistosomiasis: “Digging Their Graves with Their Forks”. Pathogens 2024, 13, 482 - Ange W. Embo-Ibouanga; Michel Nguyen; Jean-Patrick Joly; Mathilde Coustets; Jean-Michel Augereau; Lucie Paloque; Nicolas Vanthuyne; Raphaël Bikanga; Anne Robert; Françoise Benoit-Vical; Gérard Audran; Philippe Mellet; et al. (Pathogens)
There was an error in the original publication [...]